Balancing the wisdom tree: Anthology of ftii's women alumni - Publications Division (New Delhi Publications Division, Ministry of Information and Broadcasting, GOI, 2024)
BALANCING THE WISDOM TREE - ANTHOLOGY OF FTII`S WOMEN ALUMNI.
Keywords: Gender Equity; Social Problems for Women